Association of ageing-related biomarkers with peripheral neuropathy in colorectal cancer patients up to 2 years after diagnosis - Wenbo Wu; Floortje Mols; Cynthia S. Bonhof; Lou Maas; Frederik-Jan van Schooten; Geja J. Hageman; Lonneke V. van de Poll-Franse; Dounya Schoormans (PLoS ONE, 2025)
Peripheral neuropathy (PN) and accelerated biological ageing are common in colorectal cancer (CRC) patients. In vitro and in vivo studies suggest links between biological ageing, oxidative stress, and PN. This longitudinal study examined associations between markers of accelerated ageing (leukocyte telomere length (LTL) and plasma NAD+ levels) and oxidative stress (protein carbonyl content (PCC)) with PN in CRC patients. Newly diagnosed CRC patients (n = 457) were recruited in a Dutch prospective cohort. LTL, plasma NAD+ levels, PCC, and PN (self-reported using the EORTC QLQ-CIPN20) were measured at baseline (prior to treatment), 1-year, and 2-years follow-up. Associations between biomarkers and PN were analyzed using a confounder-adjusted linear mixed model. Longer LTL was associated with higher PN scores, including Sensory PN (SPN) and Motor PN (MPN), while lower plasma NAD+ levels were linked to higher SPN complaints (β:-2.29;95%CI:-4.31,-.27). These associations were primarily driven by inter-individual changes over time. Among chemotherapy-treated patients, lower plasma NAD+ levels were associated with higher total PN scores, SPN, and autonomic PN symptoms. Lower NAD+ levels were longitudinally associated with higher SPN complaints, especially among those treated with chemotherapy. These findings emphasize the potential for targeting NAD+ metabolism to mitigate PN in CRC.